Back Cover. Issue 6 (21st May 2021) - Unknown
Abstract : This cover picture describes the graphene‐isolated AuAg nanocrystal (GIAAN) with SERS‐active AuAg core confined in a nanospace of few‐layer graphene shell, possessing unique Raman peaks, high SERS activity and excellent stability, for multiphase SERS analysis and multimodal cellular Raman imaging. More details are discussed in the article by Chen et al . on page 1491–1497. Abstract : This cover picture describes the graphene‐isolated AuAg nanocrystal (GIAAN) with SERS‐active AuAg core confined in a nanospace of few‐layer graphene shell, possessing unique Raman peaks, high SERS activity and excellent stability, for multiphase SERS analysis and multimodal cellular Raman imaging. More details are discussed in the article by Chen et al . on page 1491–1497.